SIGNIFICANT FACTORS FOR THE SUSTAINABLE DEVELOPMENT OF TOURISM IN GEORGIA - Piranashvili, Maka; Grdzelishvili, Nodar; Maisuradze, Ketevan (European Scientific Journal, ESJ, 2016)
In the XXI century all the efforts of mankind are directed towards the inculcation of principles of sustainable development in all the spheres. Population growth, rapid economic development and a high level of globalization caused environmental pollution, emission of dangerous gases, climate change, loss of diversity of nature, etc. It is a well-known fact that the consumption of resources during sustainable development of tourism is implemented in two ways to meet economic, social and esthetic demands and to maintain the country’s cultural originality, essential biological diversity of the environmental and substantial vital systems. Principle of sustainability and correspondent approach is urgent for tourism since the promotion of the sector mostly depends on sightseeing and activities derived from natural environment, historical and cultural heritage of a certain region. Encroachment and damage of the resources, let alone their destruction, will by and large end all the talks about tourism. It is also remarkable that maintenance and rescue of a certain part of the resources is possible by tourism uniquely.